2015
DOI: 10.3109/00016489.2015.1006335
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of initial frequency mapping within 24 hours after cochlear implantation

Abstract: Initial switch-on within 24 h was done in all patients. Good hearing gain was obtained. No major complication occurred. There was no significant difference in hearing postoperatively that was attributable to the early switch-on.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Early activation within 24 hours after surgery has been reported by our hospital [9, 12] and others [10]. A minimal access approach is critical to facilitate initial switch-on within 1 day, as this can help to minimize the degree of postoperative swelling [12]. In our series, all of the patients tolerated early activation without any complications.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Early activation within 24 hours after surgery has been reported by our hospital [9, 12] and others [10]. A minimal access approach is critical to facilitate initial switch-on within 1 day, as this can help to minimize the degree of postoperative swelling [12]. In our series, all of the patients tolerated early activation without any complications.…”
Section: Discussionmentioning
confidence: 51%
“…However, various studies investigating early activation have been published and shown the safety, feasibility and residual hearing preservation [912, 18, 19]. Early activation within 24 hours after surgery has been reported by our hospital [9, 12] and others [10]. A minimal access approach is critical to facilitate initial switch-on within 1 day, as this can help to minimize the degree of postoperative swelling [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having established potential rationale for elevated impedance in patients with EVA, perhaps the most vexing issue remains the rapid decrease in impedance in patients with EVA to levels commensurate with controls. For all patients, such early (24 h) rapid drops in impedance have been observed and reported in our previous work and verified again here (5,19,20). Theorized contributing factors were reviewed above.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it can be inferred that the timing of device activation after implantation can also affect the change in impedance. Since the e cacy and safety of early switch-on within 24 h of surgery has previously been con rmed 17 , many CI centers, including ours, have changed the switch-on protocol over the past few years from the initial tting at 3-6 weeks post-surgery to the day after surgery. Previous studies investigating the evolution of electrode impedance after early switch-on have shown inconsistent results according to the type of electrode array [18][19][20] .…”
Section: Introductionmentioning
confidence: 98%